Resistência ao arrancamento de geogrelha enterrada em areias recicladas - Oliveira, Priscila Fernanda Silva de (2020)
The construction industry is one of the most important activities for the economic and social development of a country. In this context, the techniques of using geosynthetics are gaining strength and being increasingly widespread. However, with the growth of the civil construction industry itself, a significant increase in the generation of construction and demolition waste (CDW) can be observed, which causes several environmental impacts. Currently, recycled construction and demolition waste (RCDW) has demonstrated geotechnical properties that would justify its use in reinforced soil structure (RSS) with geosynthetics. Thus, given the potential use of RCDW and geogrids, it is necessary to understand the interaction of these materials, as this is a fundamental aspect in project design. In light of this, this paper proposed to study the interaction between a geogrid usually used in RSS and recycled sands through pull-out tests performed on small equipment. For this purpose, yanking tests with the same degree of compaction and with a geogrid buried in different types of recycled and natural sands (for comparison purposes) were performed. The samples were collected in order to perform their characterization in the laboratory and to evaluate the variability of their geotechnical parameters. Image tests on recycled and natural sand were carried out to verify and compare their grain surfaces. In addition to filler materials, other factors influencing tear strength were investigated: i) variation in geogrid width and ii) moisture of filler materials. The geotechnical characterization of recycled sands showed a low variability of their properties, geotechnical characteristics that resemble natural materials and non-plastic behavior. The image tests, revealed that the recycled sands have cementation on the grain surfaces. The results of the pull tests demonstrated the influences of the various factors investigated in specific ways. Containment overloads have delimited the area of stress where the geogrid could actually be pulled out of the assembled test system. Recycled sands exhibited satisfactory results for the geogrid pull-out tests. The grain size distribution of the built recycled sand improved the characteristics of this material. Based on the results, it is possible to conclude that evaluated recycled sands are good materials to be used as backfill material in reinforced soil structure, meeting physical, mechanical and environmental requirements for this kind of work.